PENGARUH LITERASI KEUANGAN, PENGGUNAAN SHOPEE PAYLATER TERHADAP PERILAKU KONSUMTIF BELANJA ONLINE DI SHOPEE (IBU PKK DESA DUKUH MADUREJO) - Lia Nur Fadhilah (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2026)
This study aims to analyze the influence of financial literacy and the use of Shopee PayLater on the online shopping consumer behavior of housewives who are members of the PKK (Family Welfare Movement) in Dukuh Madurejo Village. The development of e-commerce accompanied by the convenience of digital payment systems encourages changes in consumption patterns, particularly through the PayLater feature that allows purchases without direct payment. This study uses a quantitative approach with a survey method. Data were collected through questionnaires from 100 respondents who actively shopped on the Shopee platform and used Shopee PayLater in the last six months. The data analysis technique was carried out using multiple linear regression with the help of SPSS version 23. The results showed that financial literacy has a positive and significant effect on the consumer behavior of housewives. In addition, the use of Shopee PayLater was also proven to have a positive and significant effect on consumer behavior. The coefficient of determination value shows that financial literacy and the use of Shopee PayLater are able to explain consumer behavior by 24.2%, while the rest is influenced by other factors outside the research model. These findings indicate that increasing financial literacy and wise use of paylater are important factors in controlling consumer behavior, especially among housewives as family financial managers.